Water Sustainability and Financial Performance of Firms Listed on the Johannesburg Stock Exchange (JSE): Array - Dzomonda, Obey; Fatoki, Olawale (Acta Universitatis Danubius. Œconomica, 2021)
Objectives: The major purpose of this study was to examine the relationship between water sustainability and financial performance. Prior Work: Empirical research about water sustainability and financial performance is sparse in existing literature which created a research gap for this study. Approach: The study adopted a quantitate research method using secondary data. Panel data was collected for 8 years from 32 listed companies. The panel regression model was used to run the panel data. Henceforth, the Hausman test was used to select the perfect model between the fixed and random effects model, Results: The study established a significant positive relationship between water sustainability and the share price. This means that investors value firms which are actively involved in solving the water challenge in South Africa. Implications: Practically, the findings of this study can help to raise awareness among managers of listed companies that adopting proactive water strategies can eliminate water risk while positively enhancing financial performance. The findings may also shape water sustainability policies and legislation in South Africa and Value: The novelty of this study is that it produced new empirical findings on variables that have never been tested before in South Africa which can add value to the body of knowledge.